Freedom From Outlawed Religious Subjugation: Life’s Journey of Rescued Members of Religious Cults - Trinidad, Joel Ray Louie; Sabijon, Dodelon (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study explored the lived experiences of rescued former members of the Socorro Bayanihan Services Incorporated (SBSI) in Socorro, Bucas Grande, Surigao del Norte, Philippines. Anchored on Routine Activities Theory, Differential Association Theory, and Subcultural Theory, the research aimed to examine the experiences of informants during their involvement in the religious cult, assess the impact of government intervention programs after their rescue, and identify their aspirations for improving rehabilitation and reintegration programs. A qualitative phenomenological research design was employed using transcendental phenomenology. Data were gathered through in-depth individual interviews using a validated researcher-made interview guide, supplemented by field notes and audio recordings. The participants consisted of ten rescued former SBSI members selected through purposive sampling. The findings revealed that the informants experienced coercion, manipulation, forced obedience, economic exploitation, isolation, and psychological control while inside the cult. The narratives also showed the gradual erosion of bayanihan and family values, leading to emotional distress, regret, and long-term trauma. Government intervention programs, including psychosocial support, shelter, food assistance, and livelihood aid, contributed significantly to the recovery and reintegration of the informants and their families. However, the participants emphasized the need for sustainable livelihood opportunities, long-term mental health support, housing assistance, and stronger protection measures to ensure successful reintegration and safeguard survivors from retaliation. The study concludes that cult involvement results in severe psychological, social, and economic consequences that require sustained institutional intervention and community-based support systems. The findings support Sustainable Development Goal 3 (Good Health and Well-Being) through the promotion of psychosocial recovery and mental health support, and Sustainable Development Goal 16 (Peace, Justice, and Strong Institutions) through strengthened protection, governance, and intervention mechanisms for vulnerable individuals and communities. The study contributes to social, institutional, and community sustainability by promoting survivor rehabilitation, public awareness, and evidence-based strategies for preventing exploitation and strengthening social protection systems.
Keywords: Bayanihan; Cult Victimization; Government Intervention; Phenomenology; Rehabilitation; Religious Cults; Survivor Reintegration